Peningkatan Pengetahuan Tentang Gizi dan Stunting di Maluk Sumbawa Barat - Muhammad Supriastuti; Nurul Fadhila; Rudi Pratama (Journal of Community Action, 2025)
This service aims to increase the knowledge of pregnant women and parents of toddlers regarding balanced nutrition and stunting prevention in Maluk Village, West Sumbawa. The methods used are interactive counseling, balanced nutritional eating demonstrations, parenting classes, and assistance to local cadres through the Healthy Kitchen to Overcome Stunting (DASHAT). Evaluation was carried out through pre-test and post-test questionnaires, as well as observing the feeding behavior of toddlers. The results showed a significant increase in nutritional knowledge: the participants' average score increased from 45% on the pre-test to 85% after the counseling. Observations of toddlers' eating behavior also show positive changes: the use of local nutritious ingredients increased by 60%, and the frequency of providing additional food according to recommendations increased from 30% to 75%. Parenting classes have proven effective in motivating parents to implement parenting patterns that support children's growth, while DASHAT cadres have been successful in overseeing the sustainability of balanced nutrition practices in families. Conclusion: integrated interventions of education plus local assistance have great potential in reducing the risk of stunting in this region. It is hoped that these results can be adopted by village policy makers and the health service on a wider scale.